Economic Valuation of The Sesaot Community Forest Area West Lombok Regency - Moh. Huzaini; Akhmad Jufri; Satarudin Satarudin; Putu Karismawan (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2023)
Forest resources are one of the environmental components that function as oxygen producers, carbon absorbers, erosion prevention regulators of water systems, providers of biodiversity, and temperature regulators. Recognizing the importance of forest areas for humans and other living things, research activities are needed to analyze the value of direct and indirect benefits and existence values and identify the factors that influence the magnitude of the economic value of the Sesaot community forest area. This type of research is descriptive with a quantitative approach. The research location is in the Sesaot Community Forest Area. Respondents were 135 people who lived around the forest area and were selected by purposive sampling. Data were collected through direct interviews and analyzed using the Total Economic Value formula and multiple linear regression. The study results show that the total economic value of the Sesaot Community Forest Area in West Lombok Regency is Rp. 4,528,501,000 per year consisting of the direct use value of Rp. 1,725,326,000, indirect use value of Rp. 2,735,495,000 and a current value of Rp. 67,680,000. Factors that affect the value of the Willingness to pay are income, number of dependents, age, level of education, and profession. Simultaneously all variables have an influence and are signed on the Willingness to pay for the existence of the Sesaot community forest area.